AR-GE faaliyetlerine ilişkin teşvikler ve AR-GE giderlerinin UMS-TMS kapsamında mali tablolara yansıtılması - Yavuz, Betül (My University, 2010)
Faaliyetleri, Vergisel Teşvikler, TMS 38 ÖZET AR-GE FAALİYETLERİNE İLİŞKİN TEŞVİKLER VE AR-GE GİDERLERİNİN UMS-TMS KAPSAMINDA MALİ TABLOLARA YANSITILMASI Ülkeler arasındaki gelişmişlik düzeyi kıyaslamasında kullanılan ölçülerden birisi de milli gelirden Ar-Ge faaliyetlerine ayrılan payların oranıdır. Bugün gelişmiş ülkeler arasında sayılan, dünya ekonomisine ve ticaretine yön veren ülkelerin Ar-Ge faaliyetlerine ayırdıkları kaynaklar yadsınamaz büyüklüklere ulaşmıştır. İşte bu aşamada Ar-Ge faaliyetlerine ayrılan kaynakların büyüklüğü hem ülkelerin gelişmişlik düzeyini göstermekte hem de ülkelerin gelişme yolundaki itici kuvveti olmaktadır. Ar-Ge faaliyetlerine daha fazla kaynak ayırmak katma değeri daha yüksek ürünler elde etmeyi veya aynı ürünü daha az maliyetler ile üretmeyi sağlamaktadır. Bu nedenle tüm ülkelerde Ar-Ge faaliyeti ve projelerinin teşviki ve Ar-Ge faaliyetlerine ayrılan kaynakların arttırılması amacıyla bir takım vergisel indirim ve kolaylıklar sağlanmaktadır. Ayrıca işletmelerin mali tablolarında ciddi bir konumda bulunan Ar-Ge harcamalarının işletmeler tarafından farklı biçimlerde kaydedilmesi, işletmeyle ilgilenen tarafların yanlış ve tutarsız bilgilendirilmelerine yol açacağından, dünyada ve Türkiye’de bu konuyla ilgili düzenlemeler getirilerek yapılacak farklı uygulamalar bir standart altına alınmaya çalışılmaktadır. Bu çalışma ile Türkiye’de Ar-Ge faaliyetlerine yönelik olarak uygulanan vergisel teşvikler incelenmiş, Ar-Ge giderlerinin Uluslararası Muhasebe Standartları ve Türkiye Muhasebe Standartları kapsamında mali tablolara alınması değerlendirilmiştir. Research and Development Activities, Tax Incentives, IAS 38

INCENTIVES FOR RESEARCH AND DEVELOPMENT (R&D) ACTIVITIES AND TRANSFERING OF R&D EXPENDITURES INTO THE FINANCIAL TABLES COMPLIED WITH INTERNATIONAL ACCOUNTING STANDARTS (IAS) – TURKISH ACCOUNTING STANDARTS (TMS) One of the criteria, used in the comparison of the level of development among the countries is the rate of shares, allocated for R&D activities. The resources that the countries, deemed to have taken place among the developed countries and directing the world economy in this respect, allocate for the R&D activities from the national income have already reached undeniable growths. At this very stage, the growth of the sources, allocated for the R&D activities, indicates the level of development of the countries on the one hand and becomes a driving force in the development path of the countries on the other. The allocation of further resources for the R&D activities ensures the obtainment of products having higher added value or production of the same product with lower costs. As a consequence, various numbers of tax incentives and eases are provided in order to encourage the R&D activities and their projects and increase the sources, allocated for the R&D activities in all countries. Furthermore, since the entry of the R&D expenses that has a serious status in the financial tables of enterprises in a different manner may cause the parties, interested in the enterprise in question, to acquire wrong and inconsistent information, the different applications due to be made in this context by bringing various arrangements with relation to the subject matter pertaining thereto in Turkey and throughout the world are tried to be taken under a standard. By means of this study, the tax incentives that are applied with relation to the R&D activities in Turkey have been examined and the inclusion of the R&D activities into the financial tables within the scope of the International Accounting Standards and Turkish Accounting Standards is evaluated accordingly.
Keywords: Araştırma Geliştirme; Muhasebe Denetimi